Heavy metals concentration of irrigation water, soils and fruit vegetables in Kota Bharu area,Kelantan, Malaysia - Aweng Eh Rak; Karimah, M. (2011)
This study was conducted to evaluate the levels of selected heavy metals in irrigation water, soils and selected fruit vegetables which were cultivated in coastal village and industrial area (light and medium industry) in Kota Bharu, Kelantan, Malaysia. Results obtained showed that, water used for irrigation in both site had the highest concentration of Boron followed by Manganese, Iron and other parameters. However, in general, the quality of irrigation water complied with the Class IV, Interim National Water Quality Standard for Malaysia, INWQS, 1985 (standard for irrigation water) except Boron, Cadmium and Manganese. The irrigation water results were also compared with the Indian Standard, where in general, all the measured parameters complied with the standards except Cadmium and Manganese. Meanwhile, the concentration of heavy metals in soils for both site also complied with the Indian Standard. In addition, the concentration of Aluminium, Iron, Boron, Zinc, Manganese, Lead and Cadmium in the vegetables for both site ranged from 0.071 – 0.22 ppm, 0.65 – 2.76 ppm, 2.1 – 2.467 ppm, 0.163 – 0.32 ppm, 0.04 – 1.2 ppm, 0.0127 – 0.268 ppm and 0.0482 – 0.1123 ppm respectively. All heavy metals analyzed in vegetables also complied with the Indian Standard, World Health Organization and EU Standards.